(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2024)
The article analyzes modern approaches to defining the terms brand and branding, notes the role of global retail brands in the global economic landscape, examines the top 10 global retail brands Walmart lnc,CostcoWholesale Corporation Amazon com lnc, Schwarz Croup, The Kroger Co, Walgreens Boots Alliance, lnc, The Home Depot, lnc, Aldi Einkauf GmbH &Co.oHG and International Services CmbH &Oo.oHG, CVS Health Corporation, Tesco PLC by operational format and other important indicators, using data from the authoritative analytical collection Global Powers of Retailing, examines the share in the total the number of companies with an annual turnover of 5-10 billion dollars, considerable attention is paid to the issue of the impact of the war on the activities of global retail brands, it is shown which of them have left the Russian market, and which are operating in Ukraine, it was established that global brands influence the Ukrainian retail market, giving consumers the opportunity to choose and access a wide range of goods and services:Walmart, Amazon, IKEA,Metro AG, A.S. Watson Group, Nike, Adidas it was concluded that the presence of global brands has a positive effect on the development and modernization of retail in Ukraine.